Chitosan/nanohydroxyapatite composite based scallop shells as an efficient adsorbent for mercuric ions: Static and dynamic adsorption studies - Hassan, Asaad F; Hrdina, Radim (International journal of biological macromolecules, 2018)
Chitosan/nanohydroxyapatite composites based on scallop shells (CP12, CP14 and CP21) were prepared with different chitosan: nanohydroxyapatite ratios (1:2, 1:4 and 2:1, respectively). Nanohydroxyapatite (P), chitosan(C) and their composites were characterized by means of TGA, XRD, N2 adsorption/desorption analysis, SEM, Zeta potential and FTIR. The BET surface area ranged between 189 and 512 m2/g. Static adsorption of Hg+2 was tested for the effect of adsorbent dosage, pH, time and initial Hg+2 concentrations indicating that maximum static adsorption capacity was confirmed by CP12 (111.6 mg/g). Static adsorption well fitted with Langmuir adsorption isotherm and Pseudo-second order kinetic models. CP12 was selected for dynamic adsorption of Hg+2 considering the effect of bed height, flow rate and the effect of Hg+2 concentrations. Maximum dynamic adsorption capacity was confirmed at bed height of 3 cm, 2.0 mL/min flow rate and 300 mg/L as Hg+2 concentration with breakthrough time (tb) and exhaustion time (te) of 9 and 21 h. Yoon-Nelson and Thomas models best described the experimental Hg+2 breakthrough curve model. After static adsorption, EDTA solution confirmed the maximum desorption efficiency. The validity of CP12 was tested through three cycles of column dynamic adsorption-desorption.
Keywords: Chitosan; Adsorption; Mercury; Water Pollutants, Chemical; rtuť; adsorpce; chemické látky znečišťující vodu; Durapatite; hydroxyapatit; nanokompozity; chitosan; Hydrogen-Ion Concentration; Nanocomposites; koncentrace vodíkových iontů